2017
DOI: 10.14254/2071-8330.2017/10-4/19
|View full text |Cite
|
Sign up to set email alerts
|

Economy of education: National and global aspects

Abstract: Abstract. Our paper focuses on the national economy of education. We assume that under the current conditions of the globalized world, the economy of education reveals its two-fold nature: on the one hand, it represents an element of the national economic system, and on the other, it is also a structural component of the global education system. Therefore, national economy of education is shaped up by both internal and external factors represented by national and international influences. We analyze here the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 8 publications
0
3
0
1
Order By: Relevance
“…The statistics showed that people in higher education have more unemployment (Maryati, 2015). It may happen because more people educated need a better job with high income (Ishchenko-Padukova et al, 2017). Regardless of the pros and cons, education is essential for labour.…”
Section: Discussionmentioning
confidence: 99%
“…The statistics showed that people in higher education have more unemployment (Maryati, 2015). It may happen because more people educated need a better job with high income (Ishchenko-Padukova et al, 2017). Regardless of the pros and cons, education is essential for labour.…”
Section: Discussionmentioning
confidence: 99%
“…Statistik menunjukkan bahwa orang yang berpendidikan tinggi memiliki lebih banyak pengangguran (Maryati, 2015). Hal ini mungkin terjadi karena semakin banyak orang yang berpendidikan membutuhkan pekerjaan yang lebih baik dengan pendapatan yang tinggi (Ishchenko-Padukova et al, 2017). Terlepas dari pro dan kontra, pendidikan sangat penting untuk tenaga kerja.…”
Section: Pembahasanunclassified
“…The high economic potentiality of the country includes high-quality human resources (HR) which are skilled, professional, effective, flexible, creative, and team-oriented. The mission of universities is to develop harmonious personality, knowledge, wisdom and also creativity to contribute to the development of education and culture for the welfare of the whole society (Ishchenko-Padukova et al, 2017;Vojtovic & Krajnakova, 2011). The transition of graduates from university to work is simply one of the most important periods in the construction of their adult life, as well.…”
Section: Theoretical Backgroundmentioning
confidence: 99%